EWS-Fli1 antisense oligodeoxynucleotide inhibits proliferation of human Ewing's sarcoma and primitive neuroectodermal tumor cells. - Tanaka, K (1997)
The translocation t(11;22) is a common chromosomal abnormality detected both in Ewing's sarcoma and in primitive neuroectodermal tumor cells. The translocation results in an EWS-Fli1 fusion gene, made up of the 5' half of the EWS gene on chromosome 22 fused to the 3' half of the Fli1 gene on chromosome 11. Recent studies have evaluated possible roles of the fusion gene products. However, the biological significance of EWS-Fli1 is still unknown. Using a competitive polymerase chain reaction technique, we show here that there might be a correlation between the expression levels of the EWS-Fli1 fusion gene and the proliferative activities of Ewing's sarcoma and primitive neuroectodermal tumor cells. When the EWS-Fli1 expression is inhibited by antisense oligodeoxynucleotides against the fusion RNA, the growth of the tumor cells is significantly reduced both in vitro and in vivo. The data further indicate the growth inhibition of the cells by the antisense sequence might be mediated by G0/G1 block in the cell cycle progression. These results suggest that EWS-Fli1 may play an important role in the proliferation of the tumor cells, and the EWS-Fli1 fusion RNA could be used as a target to inhibit the growth of Ewing's sarcoma and primitive neuroectodermal tumor with the specific antisense oligonucleotide.